Composting of municipal solid waste of Kampung Bako Sarawak - Khairuddin, Nozieana; Merais, Mohammad Sobri (Malaysian Society of Agricultural Engineers, 2019)
A preliminary study was conducted to assess the feasibility of composting of source separated organic matter of municipal solid waste (MSW) generated in areas of Kampung Bako, Kuching, Sarawak with a population over 3000. Results of MSW analysis indicate the presence of high percentage of biodegradable organic matter, acceptable moisture content and C/N ratio. On windrow composting, not only the volume of the waste was reduced but also produced a crumbly earthy smelling soil-like, compost material. All quality parameters in the compost samples were found to be within the acceptable limits set by international standard. The compost quality could further be improved by adding rice husk, poultry manure or yard waste etc. Its use in plant production or land reclamation may be helpful to maintain soil fertility and improve moisture holding capacity. MSW Composting could be adapted country wide to recycle/reuse the organic residue as solid waste management option.